China’s Crisis Bargaining in the South China Sea Dispute (2010-2013) - Ramadhani, Eryan (JAS (Journal of ASEAN Studies), 2014)
As one of China’s most intricate territorial dispute, the South China Sea dispute has sufficiently consumed significant amount of Chinese leaders’ attention in Beijing. This paper reveals that China exerts signaling strategy in its crisis bargaining over the South China Sea dispute. This strategy contains reassurance as positive signal through offering negotiation and appearing self-restraint and of negative signal by means of escalatory acts and verbal threats. China’s crisis bargaining in the South China Sea dispute aims to preserve crisis stability: a stabilized condition after escalation in which neither further escalation nor near-distant resolution is in order. From the yearly basis analysis in the four-year span study, China’s longing for crisis stability fits into its conduct in crisis bargaining with Southeast Asian states.